Optimizing the Performance of Unit IV Kamneg Satintelkam Kendal Police in Early Detection for Drawing Management - Ubedillah, Mochamad Akbar (Advances in Police Science Research Journal, 2024)
This research is motivated by the rise of weighted theft cases in various regions in Indonesia. Prevention of crime is the responsibility of the police in maintaining security and public order. One of the police units tasked with tackling theft by weighting is Unit IV of the State Security Satintelkam Kendal Police. This study aims to describe the management of State Security Unit IV, Satintelkam, Kendal Police in early detection to prevent theft by weighting. This study uses Management Theory, Competency Theory, and SWOT Analysis Theory. In this study, qualitative methods were used with a field research approach to obtain data directly by observation and using data triangulation to obtain data validity. The results of the study indicate that there are problems that affect the performance of Unit IV of the State Security Satintelkam Kendal Police in early detection in order to tackle theft by weighting. this issue is regarding the elements of management and the management process of Unit IV of the State Security Intelligence Unit, Satintelkam. The findings during this study indicate that the management of the Satintelkam State Security Unit IV needs to be improved. There are problemsolving steps in this final project, namely conducting focus group discussions, asking for assistance from the police intelligence unit, using priority scales for budgets and infrastructure, and using research in early detection activities. Make detailed planning, create job descriptions, form an intelligence network, and carry out regular anevs by discussing theft with weights.